PENGARUH PEMAHAMAN DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN : STUDI KASUS PEGAWAI SEKJEN DPD RI - Saragih, Jhon Ardiles; Wulandari, Winda (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to examine the influence of tax understanding and taxpayer awareness on individual taxpayer compliance in filing annual income tax returns. The research was conducted on employees of the Bureau of Information Systems and Documentation at the Secretariat General of the Regional Representative Council (DPD RI) using a quantitative approach. Data were collected through questionnaires distributed to 58 respondents selected via purposive sampling. The analysis employed multiple linear regression with SPSS 30.0. The results show that neither tax understanding nor taxpayer awareness has a significant partial or simultaneous effect on taxpayer compliance. The adjusted R ² value of 0.010 indicates that the two independent variables explain only 1% of the variation in compliance behavior. These findings suggest that other factors beyond tax knowledge and awareness, such as digital tax service efficiency, enforcement, or trust in government, may better explain taxpayer compliance, particularly in bureaucratic environments with automatic withholding systems.